Research on Three-phase Unbalanced Overvoltage Suppression Method Based on Active Inverter. Issue 5 (January 2021) - Li, Yibo; Cao, Wensi
Abstract: A three-phase unbalanced overvoltage suppression method based on active inverter is proposed for the three-phase unbalanced voltage caused by the imbalance of three relative parameters in the power grid. According to the zero-sequence current generated by the neutral point in the three-phase unbalanced state in the system, the tracking inverter circuit is correspondingly injected with a certain magnitude and phase current to compensate the three-phase unbalanced current without changing the grid-to-ground insulation. Under the condition of parameters, the three-phase unbalanced overvoltage is quickly and accurately suppressed, and the three-phase voltage balance of the grid is forced. Due to the complex and variable structure of the distribution network, the three-phase unbalance phenomenon is particularly prominent. Therefore, the distribution network is very representative. The reliability of the proposed method is verified by simulation analysis.